Stabilitas Hasil Galur Baru Padi Sawah Preferensi Konsumen Sumatera Barat - ZEN, SYAHRUL (AGRITROP; Vol. 26, No. 1 Maret 2007, 2012)
Total rice field area in West Sumatera is 221.165 ha. The largest portion of irrigated rice is on 0 – 1200 m asl. The major preference of Indonesia rice consumers, the West Sumatera consumers prefer high amylose content rice. The availability of rice variety with high amylose is very limited; consequently, the dominant varieties planted by the farmers were Cisokan and IR 42 that has been cultivated for more than 1 0 years. By single variant analyze for genotype yield data were absolutely different. According to average yield of 21 grows environment, SPR85163-5- 1-2-4 line and S4362f-Kn-2-1-2 showed the sheet for each line 10 and 18% higher than Cisokan. The yield of both variants were 4.68 – 7.62 t/ha and 3.24 – 7.83 t/ha, with average of yield was 6.06 and 6.48 t/ha, whereas Cisokan yield was 3.32 – 7.89 t/ha with average of yield was 5.49 t/ha. According to data of turn yield and cross average of environment grow SPR85163-5-1-2-4 line was superior in yield capacity and adaptation then Cisokan. In certain environment grow; line S4362f-Kn-2-1-2 had the lower sheet yield than Cisokan and SPR85163-5-1-2-4. Stability parameter analyze indicate that all genotype that were tested gave the stable respond to chance of condition in 21 environment grow, SPR85163-5-1-2-4 line was more stable than line S4362f-Kn-2-1-2, that was indicated by contribution of each. Interaction of variant component Genotype x environment (interaction of G x L) for each component was 15 and 23 %. The line of SPR85163-5-1-2-4 was able to yield 20% higher than line S4362f-Kn-2- 1-2 and 26% Cisokan variety at Guguk environment (850 a above se level), while SPR85163-5-1-2-4 line has the best result until 700 m above sea level.
Keywords: Yield stability, consumers preference, new line